Monocular location primitives used to evaluate horizontal disparity in local stereopsis - Petrauskas, V.; Vaitkevičius, H.; Mildažis, V. (Psichologija, 1995)
Depth perception of two point-like stimuli presented dixoptically was studied as a function of luminance distribution within the pair of stimuli in each half-field. The dots subtended approximately l arcminute and were separated by 3, 4, 5 or 6 arcminutes. The depth changed gradually unless the separation between the stimuli exceeded 4 arcminutes. The depth change cannot be derived solely on the basis of disparity change. The results may be accounted for if assumed that disparity is evaluated by the difference in the weighted mean (centroid) of luminance distribution over corresponding left and right retinal regions.
Keywords: monocular location primitives; horizontal disparity; local stereopsis